Bagaimana Inflasi, Suku Bunga Dan Performa Keuangan Mempengaruhi Return Saham - Santi Widyaningrum; Sahala Manalu; Grace Syema Jessia (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
According to the 2019 Indonesian trade statistics report, CPO, a product produced on plantations, was Indonesia's top export. In comparison to other sectors, the price movement of the plantation sector index exhibited increased volatility in the years between 2018 and 2020. The aim of this study is to investigate macroeconomic and microeconomic factors as they are revealed by changes in inflation, interest rates, and financial performance. Profitability ratios, activity ratios, leverage ratios, and liquidity ratios are the ratios that demonstrate financial performance and are evaluated using ROE, TATO, DER, and CR. To prevent errors in the traditional assumption test, multiple linear regression with the Weighted Least Square transformation is the analysis method employed. The findings revealed that ROE and TATO had a favorable impact, but inflation and interest rates had a negative impact.